Determinants of Intention to Use Eco-Friendly Bags of People in Vietnam when Shopping - Loan, Nguyen Thi Cam; Giang, Tran Thi Tra; Phuong, Tran Thi Ngoc; Anh, Nguyen Tran Tu; Huyen, Nguyen Thi; Nhung, Tran Thi Lan (Journal of Posthumanism, 2025)
This study explores the factors influencing Vietnamese consumers' intention to use eco-friendly bags when shopping. Adopting the extended Theory of Planned Behavior (TPB), the model incorporates environmental aspects. A survey of 504 participants was analyzed with Smart-PLS. Results show that environmental awareness, environmental concern, attitude, perceived behavioral control, and subjective norms significantly affect the intention to adopt eco-friendly bags. Attitude also mediates the effects of awareness and concern on behavioral intention, highlighting their importance in encouraging eco-conscious behavior. The findings suggest that raising public environmental awareness and concern is crucial for fostering sustainable habits. Policymakers should enhance environmental education across all levels, shape positive consumer attitudes, and support the availability and affordability of eco-friendly products. In addition, utilizing influential figures and tailored communication can strengthen social norms favoring green practices. These insights offer practical implications for promoting sustainable consumption in emerging economies.